Kritik Hukum atas Ratio Decidendi Patriarkal Hakim terhadap Perempuan dalam Kasus KDRT - Dini Aminarti Utomo; M. Alfami Syafultra; Hilfia Itsarova Fahlevi (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
Law is an instrument that ideally guarantees justice within every social structure, without being bound to identity, personality, and gender. However, in practice, the law often does not align with reality. Several deviations from the principles of justice have been found, including unbalanced legal considerations (Rasio Decidendi), particularly in judges' decisions concerning cases involving men and women. This research is based on how patriarchal bias is manifested in the ratio decidendi in domestic violence cases and the feminist legal concepts that can be used to assess and correct patriarchal rationality regarding female victims of domestic violence. This observation uses a normative juridical method through an approach that refers to legal norms as the main material in the law-making process. The final result of this research indicates that in several court decisions, The law often does not apply neutrally; judges' ratios decidendi often normalize domestic violence and frequently place women in a subordinate position.